2022
DOI: 10.1038/s41380-022-01692-7
|View full text |Cite
|
Sign up to set email alerts
|

A short period of early life oxytocin treatment rescues social behavior dysfunction via suppression of hippocampal hyperactivity in male mice

Abstract: Early sensory experiences interact with genes to shape precise neural circuits during development. This process is vital for proper brain function in adulthood. Neurological dysfunctions caused by environmental alterations and/or genetic mutation may share the same molecular or cellular mechanisms. Here, we show that early life bilateral whisker trimming (BWT) subsequently affects social discrimination in adult male mice. Enhanced activation of the hippocampal dorsal CA3 (dCA3) in BWT mice was observed during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Region-specific OXTR knock-down/rescue experiments will be necessary to show a causal link between OXTR levels in these regions and the expression of specific Magel2 -KO behavioral phenotypes. Indeed, in mice with a CA2/CA3 region specific OXTR knock-down, the neonatal administration of OXT did not rescue social alterations ( Pan et al, 2022 ) while, in Dysbindin -KO mice, a mouse model of schizophrenia with altered OXTR levels in the CeA, the manipulation of OXTR within this region rescued emotional recognition deficits ( Ferretti et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Region-specific OXTR knock-down/rescue experiments will be necessary to show a causal link between OXTR levels in these regions and the expression of specific Magel2 -KO behavioral phenotypes. Indeed, in mice with a CA2/CA3 region specific OXTR knock-down, the neonatal administration of OXT did not rescue social alterations ( Pan et al, 2022 ) while, in Dysbindin -KO mice, a mouse model of schizophrenia with altered OXTR levels in the CeA, the manipulation of OXTR within this region rescued emotional recognition deficits ( Ferretti et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the postnatal life, neuronal circuits are undergoing maturation at different times, and under the influence of different external and internal factors. Within these factors, OXT is believed to play a modulatory and integratory role on sensory inputs, allowing to shape brain circuits and connectivity ( Grinevich and Stoop, 2018 ; Muscatelli et al, 2022 ; Pan et al, 2022 ). It has been demonstrated that, in mouse pups, sensory experience influences OXT production and that OXT shapes neuronal circuitry by modulating spontaneous and evoked activity ( Zheng et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This test comprised of two phases, a training or familiarization phase and a testing phase separated by 1 hour of delay [32]. During the training phase of 12 minutes, mouse was put into an arena and presented with two oppositely placed identical objects.…”
Section: Novel Object Recognition Testmentioning
confidence: 99%
“…The oxytocin system is well-established for its role in promoting social interactions, including parent-infant interactions and pair bonding (Benjamin and Neumann, 2018;Insel, 2010;Marlin et al, 2015;Valery and Ron, 2018;Walum and Young, 2018). In the social interactions among same-sex peer mice, social recognition is also reported to be regulated by the hippocampal oxytocin receptor (OXTR) Pan et al, 2022;Raam et al, 2017;Tsai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The oxytocin system is well-established for its role in promoting social interactions, including parent-infant interactions and pair bonding (Benjamin and Neumann, 2018; Insel, 2010; Marlin et al, 2015; Valery and Ron, 2018; Walum and Young, 2018). In the social interactions among same-sex peer mice, social recognition is also reported to be regulated by the hippocampal oxytocin receptor (OXTR) (Lin et al, 2018; Lin and Hsu, 2018; Pan et al, 2022; Raam et al, 2017; Tsai et al, 2022). Interestingly, a recent research has unearthed a disparity in the necessity of Oxtr function for pair bonding and parental behaviors in prairie voles (Berendzen et al, 2023), implying potential species-specific variations in the roles played by the oxytocin system in social bonding.…”
Section: Introductionmentioning
confidence: 99%